I. Note on Dr. Machlup's Article - Friedman, Milton (Review of Economic Studies, 1936)
Journal Article Further Notes on Elasticity of Substitution: I. Note on Dr. Machlup's Article Get access Milton Friedman Milton Friedman Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 2, February 1936, Pages 147–148, https://doi.org/10.2307/2967506 Published: 01 February 1936